2005
DOI: 10.1055/s-2004-830514
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Framework for Performance Diagnosis and Training Prescription from Submaximal Gas Exchange Parameters - Theory and Application

Abstract: The first part of this article intends to give an applicable framework for the evaluation of endurance capacity as well as for the derivation of exercise prescription by the use of two gas exchange thresholds: aerobic (AerTGE) and anaerobic (AnTGE). AerT GE corresponds to the first increase in blood lactate during incremental exercise whereas AnTGE approximates the maximal lactate steady state. With very few constraints, they are valid in competitive athletes, sedentary subjects, and patients. In the second pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
408
3
46

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(473 citation statements)
references
References 134 publications
(195 reference statements)
16
408
3
46
Order By: Relevance
“…If a runner achieved O 2 max during a stage that was not maintained for 1 min, the velocity during the previous stage was considered to be the minimal velocity to elicit the O 2 max. The RCP was determined by three independent investigators as the point of a nonlinear increase in the e/ CO 2 , a constant increase in the e/ O 2 , and the first decrease in the expiratory fraction of CO 2 [17].…”
Section: Secondary Outcome Variables: Cardiorespiratory Parameters Anmentioning
confidence: 99%
See 1 more Smart Citation
“…If a runner achieved O 2 max during a stage that was not maintained for 1 min, the velocity during the previous stage was considered to be the minimal velocity to elicit the O 2 max. The RCP was determined by three independent investigators as the point of a nonlinear increase in the e/ CO 2 , a constant increase in the e/ O 2 , and the first decrease in the expiratory fraction of CO 2 [17].…”
Section: Secondary Outcome Variables: Cardiorespiratory Parameters Anmentioning
confidence: 99%
“…Endurance running performance exhibits a well-documented association with several physiological parameters such as maximal oxygen uptake ( O 2 max), respiratory compensation point (RCP), and time to exhaustion at the velocity corresponding to O 2 max (T lim ) [3,14,17]. Over the past three decades, a wide number of studies have reported beneficial effects of traditional strength training (ST) on these endurance parameters [12,13,18,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…O primeiro limiar, conhecido como limiar aeróbio, reflete a intensidade do exercício correspondente ao início do acúmulo de lactato sanguíneo, e também pode ser chamado de primeiro limiar ventilatório (LV 1 ). O segundo limiar é considerado o ponto de compensação respiratória 6 ou segundo limiar ventilatório (LV 2 ), definido como a intensidade de esforço acima da qual a produção de lactato supera sua própria remoção, provocando hiperventilação, necessária para a diminuição da pressão parcial de dióxido de carbono (PCO 2 ) venosa e para o restabelecimento das concentrações de bicarbonato (HCO 3-), aumentando o pH plasmático [7][8] . Estas duas variáveis (VO 2max e LV 2 ) são consideradas parâmetros fundamentais na definição da capacidade aeróbia de um indivíduo 9 e, embora testes de campo possam ser empregados para estimação de tais variáveis metabólicas, a ergoespirometria consiste em um confiável método não-invasivo capaz de determinar com considerável precisão o VO 2max e o LV 2 pela quantificação das trocas gasosas realizadas pelo avaliado durante o exercício 1 .…”
unclassified
“…El VO 2máx fue recogido como el valor más alto de consumo de oxí-geno en un intervalo de 30 segundos a lo largo del test incremental. El VT 1 fue determinado como la carga de trabajo correspondiente a un incremento tanto en VE•VO 2 -1 y en la PetO 2 , sin un aumento concomitante del VE•VCO 2 -1 , mientras que la determinación del VT 2 se realizó cuando se produjo un incremento tanto en el VE•VO 2 -1 como en el VE•VCO 2 -1 (Davis, 1985;Lucía, Hoyos, Pérez, & Chicharro, 2000;Meyer, Lucía, Earnest & Kinderman, 2005;Pérez et al, 2006). Dos investigadores de forma independiente determinaron VT 1 y VT 2 .…”
Section: Tests Cardiorrespiratorios Máximosunclassified